The incidence and outcome of ischemic colitis in a population-based setting. (3rd July 2017) - Yngvadottir, Y.; Karlsdottir, B. R.; Hreinsson, J. P.; Ragnarsson, G .; Mitev, R. U. M.; Jonasson, J. G.; Möller, P. H.; Björnsson, E. S.
Abstract: Objective: Population-based studies on patients with ischemic colitis (IC) are limited. We aimed to determine the incidence, risk factors and outcome of patients with IC. Methods: A retrospective nationwide study was conducted on adult patients with histologically confirmed IC in 2009–2013 in Iceland. IC patients were matched for age and gender with patients hospitalized with lower gastrointestinal bleeding. Data were collected on clinical presentation, comorbidities, smoking habits, management and outcome. Results: Eighty-nine patients, 61 (69%) females and mean age of 65 years (±17), fulfilled the predetermined criteria. Females were older than males, 68 years (±14) vs. 59 years (±20) ( p  = .0170). The mean cumulative incidence was 7.3 cases per 100, 000 inhabitants. A total of 57 (64%) patients presented with abdominal pain, hematochezia and diarrhea. IC was localized in the left colon in 78 (88%) patients. Overall, 62 (70%) patients had cardiovascular disease vs. 53 (60%) of control group (NS) and 55 (62%) had a history of smoking vs. 53 (60%) in control group (NS). Ten (11%) patients required surgery and/or died within 30-days from hospital admission. At the end of follow-up, 7 (9%) patients had experienced recurrence of IC with an estimated 3-year recurrence rate of 15%. Conclusions: IC is a common clinical phenomenon that affects a wide range of age groups, but is most prominent among elderly women. It typically presents with a clinical triad of abdominal pain, hematochezia and diarrhea. Most cases are mild and self-limiting with a good prognosis.